Photophysical properties of novel luminescent dyes: difluoroborate complexes of benz[c,d]indole derivates - Navozenko, O.M.; Yashchuk, V.M.; Slominskii, Yu.L.; Kachkovsky, O.D.; Naumenko, A.P.; Myagchenko, Y.O. (Functional Materials, 2012)
The fluorescence and absorption spectra of new boron-containing dyes have been studied. Using standard techniques, the quantum yield and fluorescence decay characteristics for these substances in liquid solutions were determined. It has been shown that these dyes in solutions are characterized by high quantum yield. The full interpretation of the absorption and fluorescence spectra has been done using quantum-chemical calculations. It is established that superposition of the fluorescence spectra dyes covers almost the entire visible range of wavelengths. The absorption region can be varied by changing the end groups in these dyes. Dyes with these properties can be used for creation of white OLEDs.